DIVERSITY MANAGEMENT IN THE CZECH REPUBLIC: THE FOCUS ON UKRAINIAN REFUGEES - Medová, Mgr. Nikola; Macková M.A., Lucie (MIGRATION POLICY AND LEGAL RESPONSES, 2025)
Diversity management has become an increasingly prominent topic within Czech society, especially in light of the recent influx of Ukrainian refugees following the Russian invasion of Ukraine in February 2022. The Czech Republic has been compelled to implement a range of new policies and measures to address the urgent challenges arising from this migration situation. Among these challenges, the integration of Ukrainian children into the Czech educational system has emerged as a central issue, sparking public debate on inclusion and social cohesion. This paper examines the current situation of Ukrainian refugees in the Czech Republic, with a particular focus on evolving public attitudes toward their inclusion and the broader implications for diversity management in Czech society.